Contribuições da interação da teoria das opções reais e do Target Costing à definição de um processo de precificação que maximize o resultado da empresa - Souza, Rubens Feitosa de (2013)
The aims of this work is to show the contributions that the interaction between real options theory and target costing may offer in the pricing process. The justification for this issue lies in the lack of studies on the subject, because there are many works on the target costing and the real options theory, however, in the literature no studies were found that explicitly describe the interaction between the real options theory and target costing. To get to the objective of the work, spoke out about the pricing from the perspective of cost, the investment analysis and the economic viewpoint, it was demonstrated throughout the work the various techniques and theories on pricing, supported on a deductive method, descriptive and exploratory. At the end of the work, using the assumptions of target costing as premises of managerial flexibility of real options theory, proved a great contribution to the pricing process because decision makers might have a far more complete variables that impact the price and make the right decision on market possibilities